Deconstructing the South African National Curriculum Framework : to what extent are UDL principles incorporated into the curriculum to ensure it is differentiated for children with disabilities? - Samuels, Alecia (University of Pretoria, 2022)
Mini Dissertation (MAAC)--University of Pretoria, 2021.